Porosity changes in progressively pulverized anthracite subsamples: Implications for the study of closed pore distribution in coals. (1st August 2018) - Chen, Yilin; Qin, Yong; Wei, Chongtao; Huang, Lili; Shi, Qingmin; Wu, Caifang; Zhang, Xiaoyang
Abstract: Coal samples for low-pressure nitrogen (N2 ) adsorption measurement in previous work cover a large particle size range (from 0.075 to 4.75 mm). However, minimal attention has been paid to the effect of coal particle size on pore structure using gas adsorption methods. Anthracite coal collected from the Zhina Coalfield, China, was crushed, subsampled, and sieved to eight particle size ranges: 1–2 mesh (8000–25400 µm), 40–50 mesh (270–380 µm), 50–70 mesh (212–270 µm), 70–90 mesh (160–212 µm), 90–160 mesh (96–160 µm), 160–200 mesh (75–96 µm), 200–300 mesh (48–75 µm), and >300 mesh (<48 µm). The adsorption–desorption isotherms of each subsample were measured using N2 at 77.35 K to compare differences in pore structure characteristics. The results of the N2 adsorption tests show that particle size has a significant effect on pore volume, specific surface area, and pore size distribution of coal. Specifically, decreasing coal particle size results in continuous increase in macro- and mesopore volumes and specific surface areas. This can be attributed to the fact that smaller-sized coal particles open more of the previously closed pores, which are then accessible to adsorping gas. The contribution of closed pores to the total pore volume is 94.94% in the pore aperture range of 3.1–370 nm. The volume of closed macropores varies from 48.96 to 84.69% of the total closed pore volume. According to optical microscope and SEM observations of the Zhina Coalfield subsamples, massive gas pores exist in an isolated form with poor connectivity; some plant tissue pores are filled by pyrites and clay minerals, and may be totally occluded. Thus, gas pores contribute the dominant amount of the closed pore volume. In addition, different Zhina Coalfield subsamples show varied hysteresis loop shapes, indicating that closed pores in coal possess a variety of pore morphologies and sizes. To improve the accuracy and comparability of the pore structure of coal, we propose >300 mesh as the preferred particle size of coal for all low-pressure N2 adsorption measurement in future work. Furthermore, caution must be used in evaluating coal bed methane resource recovery potential as coal possesses high closed porosity; failure to account for this will result in an overestimation of the amount of gas that can be recovered from coal seams during production.